2018
DOI: 10.1111/are.13954
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium yeast, tributyrin and bile acid on growth performance, digestion and metabolism ofChanna argus

Abstract: A 60-day feeding trial was carried out to evaluate the effects of chromium yeast (CY), tributyrin (TB) and bile acid (BA) on the snakehead (Channa argus). The control (CT) group was fed the basal diet, and the experimental groups were fed 200 mg/kg CY (concentration: 1,000 mg/kg), 2.5 g/kg TB (purity: 45%) or 1 g/kg BA (purity: 30%) in addition to the basal diet. The addition of CY, TB and BA statistically increased the weight gain rate, and specific growth rate, whereas the feeding rate and feed conversion ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 56 publications
8
31
0
Order By: Relevance
“…TB supplementation in tawny puffer diets had been reported that WG, SGR, feed efficiency (FE), and protein efficiency ratio (PER) of fish were increased with the increasing TB level, and the greatest values of them were found in 1.0 g kg −1 groups (Zhai et al., 2014). Dietary TB also has been reported to positively affect the growth performance of snakehead (Hou et al., 2019). Recent studies showed that an appropriate dietary TB level improved the growth performance of black sea bream (2.0 g kg −1 –4.0 g kg −1 ) and yellow drum (1.0 g kg −1 –2.0 g kg −1 ) fed high‐soya bean meal diets (Tan et al., 2020; Volatiana, Wang, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TB supplementation in tawny puffer diets had been reported that WG, SGR, feed efficiency (FE), and protein efficiency ratio (PER) of fish were increased with the increasing TB level, and the greatest values of them were found in 1.0 g kg −1 groups (Zhai et al., 2014). Dietary TB also has been reported to positively affect the growth performance of snakehead (Hou et al., 2019). Recent studies showed that an appropriate dietary TB level improved the growth performance of black sea bream (2.0 g kg −1 –4.0 g kg −1 ) and yellow drum (1.0 g kg −1 –2.0 g kg −1 ) fed high‐soya bean meal diets (Tan et al., 2020; Volatiana, Wang, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the beneficial effect on the growth production, dietary butyrate also showed a positive effect on fish physiological and biochemical profiles related to the body function and health status (Bedford & Gong, 2018; Hou et al., 2019; Luz et al., 2019; Ng & Koh, 2017). Since plant ingredients have various ANF and non‐starch polysaccharides (NSF), dietary plant proteins often disturbed the digestibility of fish resulting in decreased intestinal absorption, and this situation can worsen with increased incorporations of plant‐based proteins in aquafeeds, but also may be mitigated by the dietary inclusion of butyrate (Gao et al., 2011; Volatiana, Wang, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…intestinal digestive and barrier functions in several studies (Hou et al, 2006(Hou et al, , 2019Tan et al, 2020;Volatiana, Sagada, et al, 2019;Volatiana, Wang, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%